2002
DOI: 10.1017/s1323892200000685
|View full text |Cite
|
Sign up to set email alerts
|

Claims / Injury Management and Rehabilitation for Injured Workers: Initial Results of a Partnership Approach

Abstract: Acritical life event such as a significant work injury imposes on the individual a heavy burden in terms of suffering, social exclusion, stigmatisation, negative role transition, and emotional, and financial costs. Such events, therefore, have multi-level implications relating to the functional restoration of workers, the professional efficacy of their service providers, industry productivity and economic viability at individual, organisational, community and state levels. In accord with this viewpoint, discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…The researcher's familiarity with the area allowed effective management of the high volume of data in relation to the key issues. The distinct perspectives of different stakeholders can be seen in the resulting publications (see Roberts-Yates 2002a, 2002b, 2003a, 2003b, 2003c, 2004. The comments quoted in the introductory material above also come from this source.…”
Section: Research Findings Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The researcher's familiarity with the area allowed effective management of the high volume of data in relation to the key issues. The distinct perspectives of different stakeholders can be seen in the resulting publications (see Roberts-Yates 2002a, 2002b, 2003a, 2003b, 2003c, 2004. The comments quoted in the introductory material above also come from this source.…”
Section: Research Findings Methodologymentioning
confidence: 99%
“…It is clear that there is a need for an overall assessment of future possibilities in the delivery of improved responses in relation to claims/injury management and rehabilitation in South Australia. Recent publications have outlined concerns and issues in claims/injury management and rehabilitation (Roberts-Yates 2002a, 2002b, 2003a, 2003b, 2003c, 2004a. This article addresses the issue of identifying the key aspects of the situation to which attention should be paid immediately.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Assumptions were identified from the researcher's prior experience and knowledge of the field, and anecdotal evidence was acquired from the key stakeholders. The stakeholder groups were invited to comment, validate and modify the prepared list of assumptions resulting in a series of key perceptions from which the key research questions were identified (see Roberts-Yates, 2002a). The interviews were guided by semi-structured questions where appropriate and at other times prompts were constructed to encourage narrative and discussion.…”
mentioning
confidence: 99%
“…(7,222,350) Workers in these systems felt they lacked information explaining the compensation process, or the information was provided in language that was difficult to understand. (222,414) Using a framework of loss may be a way of considering some of the key psychosocial, emotional and physical aspects that impact on a workers' recovery and cause barriers to returning to work. Hence, a worker-centric paradigm has been proposed as one method to improve workers' experiences in their RTW journey.…”
mentioning
confidence: 99%